A collaborative approach to in-situ oxysulfides and oxynitrides fixation in flue gas and energy recycling: Co-combustion of spent bleaching earth and coal. (10th June 2020) - Yuan, Zhihang; Shen, Yaoya; Yuan, Haiping; Sui, Aimin; Zhu, Nanwen; Lou, Ziyang
Abstract: Spent bleaching earth (SBE) with high pollutant-producing coefficient was generated from lubricating oil refining and aviation kerosene hydrogenation unit in the oil refinery, while the disposal processes were limited due to its hazardous properties in the city. A simple and efficient approach was developed to co-combust SBE and coal in the company inner power plant, and synergetic effect was observed in SO2 and NOx reduction in flue gas and energy recycling of waste oil. The full-cycle combustion process was investigated in details under different mixing ratio of the two substances from 0 to 1000 °C. According to the TG/DSC-MS results, it was found that the introduction of SBE could reduce the decomposition temperature of coal from 475-931 °C to 450–815 °C, since the dehydrogenation and decarboxylation effects of metallic oxides and the high contacting area with oxygen provided by the porous structures of SBE. The tubular electric heating furnace-FTIR results showed that the concentration of typical pollutants in flue gas decreased obviously at the coal/SBE mixing ratio 5:1, among them, the maximum SO2 emissions reduction reached 32%. The chemical adsorption effect of alkaline earth metals and transition metal oxides and oxidation-reduction reaction between NO + NO3 − and SO3 2− were proved as the main fixation mechanisms. The regenerated porous structures in SBE provide new adsorption site after the volatilization of adsorbed oils, so as to further enhance the fixation capacity. Co-combustion process of SBE and coal offered a promising way for simultaneous in-situ gaseous pollutant control in flue gas and energy recycling from SBE. Graphical abstract: Image 1 Highlights: SBE possesses catalytic effect on the ignition temperature reduction of coal. The addition of SBE can reduce the emission of oxysulfides and oxynitrides from coal. The main fixation mechanism of oxysulfides and oxynitrides is chemisorption and redox. Co-combustion with coal is a promising pathway for the disposal and resource utilization of SBE.